UJI QUALITY CONTROL PESAWAT MAGNETIC RESONANCE IMAGING SIEMENS MAGNETOM CONCERTO 0,2 TESLA DI INSTALASI RADIOLOGI RSUD DR KANUJOSO DJATIWIBOWO BALIKPAPAN - Luh Deva Wedayanti; Nurdopo Baskoro; Sudiyono Sudiyono (Poltekkes Kemenkes Semarang, 2019)
Background : Radiology quality control is a part of radiology quality assurance which is directly linked with physical measurements of facility performance and indirectly linked with the expected image quality. The advantage of proceeding with the performance test on MRI device are the consistency of operational testing that integrated of all MRI system and producing high quality image, reducing the possibility of artifact appearance, and also preemptive identification of potential problems.Methods : The method of this Research is Qualitative Survey. The researchers are doing the survey on Quality Control test on MRI device brand Siemens Magnetom Concerto 0,2T on Radiology department of RSUD. DR. Kanujoso Djatiwibowo Balikpapan.Results : The whole result of this research shows that MRI device on RSUD. DR. Kanujoso Djatiwibowo Balikpapan has yet to fulfill the international standard.Conclusion : The whole result of this research shows that MRI device on RSUD. DR. Kanujoso Djatiwibowo Balikpapan has yet to fulfill the international standard on 5 parameter, such as the SNR testing, Artifact Analysis, Geometric Accuracy, High Contrast Resolution and Low Contrast Resolution. On the other hand, 2 other parameter such as slice thickness accuracy and slice position accuracy of the MRI device has already fulfill the standard and have to improve on the 5 parameter which hasn’t fulfill the factory and international standards